Going Beyond Standard Ocean Color Observations: Lidar and Polarimetry - Jamet, Cédric; Ibrahim, Amir; Ahmad, Ziauddin; Angelini, Federico; Babin, Marcel; Behrenfeld, Michael J.; Boss, Emmanuel; Cairns, Brian; Churnside, James; Chowdhary, Jacek; Davis, Anthony B.; Dionisi, Davide; et al. (Frontiers in Marine Science, 2019)
Passive ocean color images have provided a sustained synoptic view of the distribution of ocean optical properties and color and biogeochemical parameters for the past twenty-plus years. These images have revolutionized our view of the ocean. Remote sensing of ocean color has relied on measurements of the radiance emerging at the top of the atmosphere, thus neglecting the polarization and the vertical components. Ocean color remote sensing utilizes the intensity and spectral variation of visible light scattered upward from beneath the ocean surface to derive concentrations of biogeochemical constituents and inherent optical properties within the ocean surface layer. However these measurements have some limitations. Specifically, the measured property is a only weighted-integrated values over from a relatively shallow depth, the measurements provide no information during the night and retrieval are compromised by clouds, absorbing aerosols and low Sun zenithal angles. In addition, ocaen color data provide limited information on the morphology and size distribution of marine particles. Major advances in our understanding of global ocean ecosystems will require measurements from new technologies, specifically lidar and polarimetry. These new techniques have been widely used for atmospheric applications but have not had as much as interest from the ocean color community. This is due to many factors including limited access to in-situ instruments and/or space-borne sensors and lack of attention in university courses and ocean science summer schools curricula. However, lidar and polarimetry technology will provide an complement to standard ocean color products by providing depth-resolved values of attenuation and scattering parameters and additional information about particles morphology and chemical composition. This review aims at presenting the basics of these techniques, examples of applications and at advocating for the development of in-situ and space-borne sensors. Recommendations are provided on actions that would foster the embrace of lidar and polarimetry as powerful remote sensing tools by the ocean science community.